Law of prevention of atrocities on the scheduled castes and the scheduled tribes - Naval, T R (New Delhi Concept, 2001)
The book explores the history of untouchability and prevention of atrocities on the scheduled castes and scheduled tribes. It analyses the origin of caste disabilities, problems of atrocities faced by them over centuries; traces out the causes and factors
Keywords: India-Scheduled tribes; Untouchables-India; Atrocities-India; Offenses against the person; Criminal law